ANALYSIS OF TEACHER LEARNING INNOVATIONS IN CLASS IV SDN 9 MAMBORO - Safira Ibrahim; Nur Rahmah; Rizal Rizal (Jurnal Dikdas, 2021)
This thesis discusses the Implementation of Teacher Innovation in Learning in grade IV SDN 9 Mamboro. The purpose of this study was to see the innovations made by teachers in class IV learning. The type of research used is a qualitative approach where the researcher goes directly to the field to collect data. Researchers used a sample of 1 teacher and 20 grade IV students at SDN 9 Mamboro. The data techniques used were observation, questionnaires, documentation, interviews, and field notes. The results of this study were the teacher's innovation in grade IV learning at SDN 9 Mamboro which was studied successfully. The conclusion is that in implementing learning the teacher has been able to innovate in learning using various methods, media, models and teaching materials. This can be seen from the results of the questionnaire which showed a high presentation. The suggestion of this research is that teachers and students must be creative, innovative and productive in learning. Teachers improve the quality of learning through innovation in learning, so that the quality of learning is better, students understand the material more easily, and are more enthusiastic in participating in learning.